2013
DOI: 10.1128/jcm.03321-12
|View full text |Cite
|
Sign up to set email alerts
|

Association of Neurotropic Viruses in HIV-Infected Individuals Who Died of Secondary Complications of Tuberculosis, Cryptococcosis, or Toxoplasmosis in South India

Abstract: The frequencies of 10 opportunistic DNA viruses were determined by multiplex real-time PCR in paired cerebrospinal fluid (CSF) and brain tissue of HIV-infected individuals. In the CSF, viruses were detectable in 45/55 cases: JC virus (JCV) in 62%, Epstein-Barr virus (EBV) in 44%, cytomegalovirus (CMV) in 25%, varicella-zoster virus (VZV) in 3.6%, herpes simplex virus 1 (HSV-1) in 1.8%, and human herpesvirus 6 (HHV-6) in 1.8% of cases. A single virus was detectable in 20 cases, 19 cases had coinfection with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 18 publications
1
10
0
Order By: Relevance
“…A study form our center reported JCV DNA in the CSF (62% of samples) and brain tissue samples (42% of the samples tested) from HIV-infected individuals. [21] One notable finding in our study is that all the 291 tested samples were also found negative for HHV-8 DNA. [25] There was a significant association with elevated SGPT/ SGOT serum level with high EBV and CMV loads.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…A study form our center reported JCV DNA in the CSF (62% of samples) and brain tissue samples (42% of the samples tested) from HIV-infected individuals. [21] One notable finding in our study is that all the 291 tested samples were also found negative for HHV-8 DNA. [25] There was a significant association with elevated SGPT/ SGOT serum level with high EBV and CMV loads.…”
Section: Discussionmentioning
confidence: 80%
“…In case of CMV 8 (89%) samples were genotype gB1 and 1 (11%) sample showed genotype gB2 in organ-specific samples like CSF and brain tissue samples. [21] Currently there are no reports on EBV genotypes among HIV-infected individuals from India other than our study. A recent study reported from New Delhi, India had studied the glycoprotein B genotypes in blood and urine of babies with symptomatic congenital/perinatal CMV infection and found gB 1, 2 and 3 genotypes in the population.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…As per the previous records death usually occurs within 9 to 12 months in 80% of the cases but again it depends on the time of initiation of ART and the viral load [24,25]. A previous study determined JCV DNA loads in patients with HIV and tuberculosis but did not present MRI findings [26]. This case report is of special interest because it uses both PCR and MRI to diagnose PML in a HIV positive patient with tuberculosis.…”
mentioning
confidence: 99%
“…Toxoplasma encephalitis is 1 of 3 leading focal central nervous system complications in patients with AIDS. The association of JCV and toxoplasma was reported when 41% of the HIV-infected patients had detectable JCV in CSF [8]. However, in another study performed in 331 HIV-infected adults in Zambia, none of the JCV-positive CSF had toxoplasmosis detected [9].…”
mentioning
confidence: 99%